2018
DOI: 10.1007/s00198-018-4533-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia and bone mineral density changes following denosumab treatment in end-stage renal disease patients: a meta-analysis of observational studies

Abstract: The incidence of hypocalcemia and bone mineral density (BMD) changes in end-stage renal disease (ESRD) patients on denosumab remains unclear. We performed this meta-analysis to assess the incidence of denosumab-associated hypocalcemia and effects of denosumab on BMD in ESRD patients. A literature search was conducted using MEDLINE, EMBASE, and Cochrane Database from inception through November 2017 to identify studies evaluating incidence of denosumab-associated hypocalcemia and changes in serum calcium, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 61 publications
4
31
0
1
Order By: Relevance
“…The authors stated that the decrease in PTH levels may be a result of supplements initiation (calcium and active vitamin D) after initial PTH increase within the first month. Consequently, post-treatment PTH levels were significantly lower than the baseline PTH levels [6].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The authors stated that the decrease in PTH levels may be a result of supplements initiation (calcium and active vitamin D) after initial PTH increase within the first month. Consequently, post-treatment PTH levels were significantly lower than the baseline PTH levels [6].…”
Section: Discussionmentioning
confidence: 73%
“…Lastly, a recent meta-analysis study by Thongprayoon et al used six observational studies to determine the incidence of hypocalcemia and the effects on BMD after denosumab use in ESRD patients [6]. The pooled estimated hypocalcemia incident was 42% (95% CI 29%-55%, I2 = 0%) after using denosumab in this special population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, although our studies demonstrated an association between HD status and the higher risk of hip fracture, data on BMD among ESRD patients in included studies were limited. In addition, current evidence on the benefits of interventions to improve BMD on the improvement of fracture rates in ESRD patients remains controversial . However, the findings of our study highlight the need for future studies on the prevention of hip fractures among ESRD patients undergoing HD.…”
Section: Discussionmentioning
confidence: 79%
“…Beim Einsatz in einer high turnover Situation ist unsere derzeitige Kenntnis über die Dauer der Therapie mit der Gefahr der Entwicklung eines low turnovers in der Langzeitanwendung einerseits und der Gefahr einer Steigerung des Knochenmassenverlustes nach dem Abschluss der Therapie andererseits sehr begrenzt [41,42]. Zudem wurde die Induktion einer schweren Hypocalcämie nach der Denosumab Applikation bei einer chronischen Niereninsuffizienz im Stadium CKD G4 und G5 wiederholt beschrieben [43,44].…”
Section: Osteologische Komedikation Bei Rheumatischen Erkrankungen Ununclassified